Metabolites reflect variability introduced by mesoscale eddies in the North Pacific Subtropical Gyre - William Kumler; Wei Qin; Rachel A. Lundeen; Benedetto Barone; Laura T. Carlson; Anitra E. Ingalls (Frontiers in Marine Science)
Mesoscale eddies significantly alter open ocean environments such as those found in the subtropical gyres that cover a large fraction of the global ocean. Previous studies have explored eddy effects on biogeochemistry and microbial community composition but not on the molecular composition of particulate organic matter. This study reports the absolute concentration of 67 metabolites and relative abundances for 640 molecular features, measured using liquid chromatography-mass spectrometry (LC-MS) following both targeted and untargeted approaches. This approach allowed us to better understand how mesoscale eddies impact the metabolome of the North Pacific Subtropical Gyre during two cruises in 2017 and 2018. We find that many metabolites track biomass trends, but metabolites like isethionic acid, homarine, and trigonelline linked to eukaryotic phytoplankton were enriched at the deep chlorophyll maximum of the cyclonic features, while degradation products such as arsenobetaine were enriched in anticyclones. In every analysis, the metabolites with the strongest responses were identified using LC-MS through untargeted metabolomics approaches, highlighting that the molecules most sensitive to environmental perturbation were not among the previously characterized metabolome. By analyzing depth variability (accounting for 20-40% of metabolomic variability across ~150 meters) and the vertical displacement of isopycnal surfaces (explaining 10-20% of variability across a sea level anomaly range of 40 centimeters and a spatial distance of 300 kilometers), this analysis constrains the importance of mesoscale eddies in shaping the chemical composition of particulate matter in the largest biomes on the planet.